Redefining actin dynamics of the pointed-end complex in striated muscle. Issue 9 (September 2021) - Iwanski, Jessika; Gregorio, Carol C.; Colpan, Mert
Abstract : Striated muscle is intricately designed to provide efficient and powerful muscle contractions. Recently, a long sought-after missing component of the thin filament pointed-end machinery was discovered: cyclase-associated protein 2 (CAP2). CAP2 was identified as a crucial contributor to actin polymerization, striated muscle development, and severe muscle disease when mutated.